HOW WORTHY IS DALTON’S PURSUIT OF CHEMICAL ATOMISM FOR THE PROSPECTIVE TEACHERS? A CASE OF KOTEBE UNIVERSITY OF EDUCATION, ETHIOPIA - Abayneh Lemma; Woldie Belachew (Universitas Negeri Surabaya, 2022)
Atom possesses controversial ontological accounts even in a single discipline such as chemistry. Its essence as a reality and inclusion in science education has been subjected to numerous philosophical and scientific debates. The educational literature also shows that the ancient corpuscular notion is dominantly portrayed within the curriculum and instruction of many educational settings. The fundamental problem is that the chemists, educators, philosophers, and historians of chemistry themselves haven’t had a substantial agreement on any of the philosophical and scientific accounts due to their longstanding philosophical divide between the different positions of positivism and realism. Neither has the historical perspective of philosophy and science been reasonably acknowledged in science/chemistry education. We aimed in this interpretative case study to figure out how much Dalton’s pursuit of the chemical atomism is worth to 22 purposely selected and interviewed prospective teachers. The resulting transcripts were analyzed using HPS, the seven milestones of its case study. As a result, one major and two minor themes were found none of which match any of the themes of the milestones. Moreover, the entire narrative lacks some essential perspectives and contexts of HPS in general and Dalton’s experimentations in particular. Misjudgment of his indivisibility notion, for example, is a drawback associated with this limitation. Thus, more inquiries are needed to be conducted in the long run into the curriculum and classroom practice while departmental discussions on such issues are suggested in the short run.